Analisis Kurikulum Merdeka pada Mata Pelajaran Fiqih Kelas VII di Madrasah Tsanawiyah - Nuroh, Laelatul; Ismatullah, Ade (Epistemic: Jurnal Ilmiah Pendidikan, 2023)
This research analyzes the implementation of the Merdeka Curriculum in the subject of Fiqih at Madrasah Tsanawiyah. The Merdeka Curriculum offers flexibility for educational institutions, including madrasahs, to tailor their curricula to the unique characteristics and needs of their students. This study focuses on the adaptation of Fiqih within this framework. Using a qualitative approach, the research employs curriculum document analysis, interviews, and observations in several Madrasah Tsanawiyah. The findings reveal that the implementation of the Merdeka Curriculum in the Fiqih subject has facilitated the integration of learning materials that reflect local wisdom and Islamic values. However, challenges remain, particularly in integrating learning aspects that respond to contemporary developments and students' needs. Furthermore, evaluation and teaching methods require further refinement to achieve the holistic goals of Islamic education. This research aims to provide valuable insights for education policymakers, madrasah administrators, and educators, to enhance the quality of religious education at the Madrasah Tsanawiyah level, aligning it with the broader objectives of national education development.